Sosial Determinan dan Perilaku Merokok di Indonesia (Analisa Data Riskesdas Tahun 2013) - Nurhalina Nurhalina (Borneo Journal of Medical Laboratory Technology, 2019)
Smoking is a public health problem because it can lead to various diseases for smokers and the people around him. Cigarettes kill more than half user, nearly 6 million people a year are made up of smokers and former smokers and 600 thousand non-smokers exposed to secondhand smoke. When you do not control, tobacco-related deaths will rise rapidly to 8 million in the year 2030. The prevalence of smoking in Indonesia reached 36.3% in the year 2013, and on all levels of society. Smoking trends continue to increase from year to year both in men and women alike. This paper describes the smoking behavior to describe the behavior of smoking by age, gender, place of residence, education, employment, the index quintile ownership and number of cigarettes smoked per day. The source of data is secondary data Riskesdas 2013 that comprehensively analyzed through literature review and theory. The results showed that the age of 34-54 years, male gender, residence in rural, low education and have jobs with proprietary index quintile down to lower middle is a reasonably significant determinant factor on smoking behavior in Indonesia.